Project Based Learning Model Based on Simple Teaching Tools and Critical Thinking Skills - Sri Wahyu Widyaningsih; Irfan Yusuf (Kasuari: Physics Education Journal (KPEJ), 2018)
This study aims to determine the application of PjBL model based on simple props and criticalthinking skills of students in the School Laboratory course. This research uses research type Pre-Experimental Design with sample of all students of semester II which programmed Laboratory School oneven semester 2016/2017 in Program Studi Pendidikan Fisika Fakultas Keguruan dan Ilmu PendidikanUniversitas Papua. The results showed that the props designed by students 74.0% ± SD 4.2 or are in agood category. Assessment of practical worksheet covers the aspect of format, content, language/writing,and benefits/functions obtained 80.3% ± SD 7.4 or are in the very good category. Critical thinking skills ofthe students during the learning that is 66.7% ± SD 4.9 or are in a good category. Therefore theapplication of PjBL learning based on simple props can be used to develop critical thinking skills.